ANALISIS WACANA BERITA KORUPSI DALAM SITUS LOKAL (Konstruksi Gagalnya Bupati Tobasa Menjalankan Pemerintahan Yang Bebas Korupsi Dalam BersamaToba.Com Periode April - November 2009) - , HILDA DAMAYANTI; , Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is based on the purpose to reveal the corruption news conducted by a Regent in the period of 2005-2010, in the regency of Toba Samosir, North Sumatera, to wit, Monang Sitorus, on a local web called BersamaToba.com. The type of research used to analyze the news, is qualitative, with a Teun Van Dijk versionâs of discourse analysis study method. The object of this research is the corruption news which was uploaded on the corruption canal of BersamToba.com, in the period of April, May, September and November 2009. Each month contains one corruption news. Tobasa, a region which was recently established as Regency in 1999, has been administered by two Regents since it was legally affirmed. A leader is properly known to have a responsible attitude and willing to conduct goodness for the sake of implementing all visions and missions hold by the Regency since the beginning. But the fact which occurred showed that both of these Regents own their track record of deceitfulness in ruling the Tobasa people. Both men were suspected to conduct a criminal act of corruption. The bustling mass medias in covering these news, was followed by a local web, which focused in gathering information in the area where they were, the website was called BersamaToba.com. This is an individual company media, with their purpose to distribute information exactly as what they witness and collect from the field, through journalistic processes, which are, collecting, analyzing and announcing the news. For the whole four months, their web posted very interesting news relating to a corruption case that was uploaded on a special canal made by the owner of BersamaToba.com to accommodate any corruption news. That canal went under the name of âcorruption.â These four news posted by them, started in April, May, September, and ended in November 1999, represented a reality that eventually formed into a real discourse, these were the speech made by the writer of that news, whom also known as the owner of BersamaToba.com website, Ivan Napitupulu. Eventually, these four pieces of news formed a certain meaning: the will of its writer to implement the real function of mass media, that is, to inform people with this corruption news occurring in Toba Samosi, with the suspect of their own Regent period 2005-2011, Monang Sitorus. This means that Monang Sitorus, as the second leader in Tobasa after the first Regent Tambun Simbolon, failed in conducting Tobasa government that is recently formed and in the expansion area. The vision and mission determined since the regency was existed in 1999 by making Tobasa as corruption-free regency has not achieved. Therefore, Tobasa people must be more selective in choosing the next leader so this regency can develop to be the regency like what Tobasa people hope.